Guidance for Efficiently Implementing Defect Causal Analysis - Kalinowski, Marcos; Travassos, Guilherme H.; Card, David N. (Anais do Simpósio Brasileiro de Qualidade de Software (SBQS); 2008: Anais do VII Simpósio Brasileiro de Qualidade de SoftwareDO - 10.5753/sbqs.2008.15540, 2008)
Defect causal analysis has shown itself to be a cheap and high return means of product-focused software process improvement. However, despite its advantages and wide industry adoption little academic research is being done in this area. Thus, professionals face several questions when implementing it in software organizations. Aiming to provide unbiased and evidence-based answers to those questions, a systematic review has been conducted. Based on the results of the systematic review, better guidance for implementing defect causal analysis efficiently in software organizations can be elaborated.